Clay-based construction and demolition waste as a pozzolanic addition in blended cements. Effect on sulfate resistance. (30th November 2016) - Asensio de Lucas, Eloy; Medina, César; Frías, Moisés; Sánchez de Rojas, María Isabel
Highlights: The influence of sulfates in blended cements based on construction and demolition waste as pozzolanic addition. The influence of sulfate concentration in durability of cementitious matrices. Changes in microstructure and morphology of cementitious matrices due to the incorporation of C&DW as pozzolanic material. The influence that C&DW as pozzolanic addition has in corrosion indices. Changes in porous network and its influence on behavior in the face of sulfate solution. Abstract: The significant structural implications of cement durability have given rise to substantial research on the subject. This study explores the performance of new blended cements bearing pozzolanic construction and demolition waste (C&DW) as an addition when exposed to sulfate attack. Durability is studied in cement pastes with and without C&DW, addressing the formation of new compounds, mechanical strength, outward appearance and porosity after soaking in two concentrations of sodium sulfate solution for exposure times ranging from 14 to 56 days. The findings confirm that the inclusion of clay-based C&DW improves blended cement durability.